Erosi senyap: Bagaimana rutinitas keseharian anak muda menggerus identitas nasional tanpa disadari - Prayogi, Rizky Bintang (Maliki Interdisciplinary Journal, 2025)
This research analyzes the phenomenon of Indonesian national identity erosion occurring through the transformation of young people's daily routines in the globalization era. Indonesia, known as a friendly and caring nation, faces serious challenges when these fundamental values experience gradual erosion through unconscious processes. Using conceptual analysis with comparative approach and theoretical development, this research explores how seemingly normal daily activities actually become the most effective medium of identity erosion. Findings show erosion occurs through: (1) language shift with excessive code-mixing dominance threatening Indonesian language as a unifier; (2) adoption of consumerist lifestyle based on social media "flexing" culture; (3) declining gotong royong participation from communal to individual values; (4) penetration of capitalist ideology changing orientation from social contribution to material accumulation. Empirical data reveals only 39.1% of youth still actively practice gotong royong, 68% understand tolerance theoretically without substantive implementation, and 47.8% experience identity crisis due to habit changes. This "silent erosion" phenomenon requires comprehensive revitalization strategies through strengthening family roles, multicultural education reform, critical digital literacy development, and stakeholder synergy to maintain Indonesian national characteristics amidst globalization currents.